Restaging of Cervical Cancer Patients Treated with Adjuvant Radiotherapy According to FIGO 2018 and Suggestions for the Next Staging: Turkish Society for Radiation Oncology Gynecologic Group Study (TROD 04-004) - ALSAN ÇETİN, İLKNUR (My University, 2022)
OBJECTIVE The objective of this study was to compare Federation of Gynecology and Obstetrics (FIGO) 2009 and 2018 staging systems in patients with uterine cervical cancer. METHODS Medical records of 571 patients who were treated with adjuvant radiotherapy or radiochemotherapy between 2001 and 2018 were retrospectively reviewed. Differences in overall survival (OS) and progression-free survival (PFS) rates according to FIGO 2009 and FIGO 2018 staging systems were compared using the log-rank test. Cox regression model was used to identify independent prognostic factors for survival. RESULTS The median follow-up was 59 months. Five-year OS and PFS rates were 81.1% and 77.7%, respectively. Stage migration was recorded in 401 patients (70.2%) and the most remarkable stage migration was detected in stage I patients (60%). A total of 157 (27.5%) patients upstaged to stage IIIC disease. According to FIGO 2009, 5-year OS rates were 87.3%, 80.5% (p=0.076), and PFS rates were 82.8%, 77.5% (p=0.036) for stage IB1 and IB2, respectively. According to FIGO 2018, the 5-year OS rates for stage IB1, IB2, and IB3 were 89.8%, 87.1%, and 81.4% (p=0.310), and PFS rates were 90.2%, 80.5%, and 80.1% (p=0.189), respectively. Patients with ≥2 pelvic lymph node (LN) metastases had worse 5-year OS and PFS rates than patients with one metastasis (p=0.015 and p=0.006). Number of para-aortic LN metastasis and metastatic LN ratio (MLNR) were also correlated with 5-year OS and PFS. CONCLUSION Current FIGO staging system better discriminates patients with cervical cancer. However, integration of metastatic LN number and/or MLNR to the upcoming FIGO staging system may improve the prognostic value of the staging.
Keywords: Cervical cancer; FIGO staging; lymph node metastasis; radiotherapy